Reaction of Bromoenones with Amidines: A Simple Catalyst-Free Approach to Trifluoromethylated Pyrimidines - Romanov, Alexey R.; Rulev, Alexander Yu.; Popov, Alexander V.; Kondrashov, Evgeniy V.; Zinchenko, Sergey V. (Synthesis, 2020)
A facile one-pot synthesis of trifluoromethylated pyrimidines has been achieved by the treatment of fluorinated 2-bromoenones with aryl- and alkylamidines. The assembly of pyrimidine core proceeds by the cascade reactions via aza-Michael addition–intramolecular cyclization–dehydrohalogenation/dehydration sequence. This strategy is featured by high selectivity and mild reaction conditions giving the target heterocycles in high yields (up to 99%). The unique influence of trifluoromethyl group on the reaction path is demonstrated.
Keywords: CF3-α-bromoenones; amidines; fluorinated pyrimidines; aza-MIRC methodology; catalyst-free; mild conditions